Trimetazidine protects against smoking-induced left ventricular remodeling via attenuating oxidative stress, apoptosis, and inflammation. - Xiang Zhou (Public Library of Science (PLoS), 2012)
Trimetazidine, a piperazine derivative used as an anti-anginal agent, improves myocardial glucose utilization through inhibition of fatty acid metabolism. The present study was designed to investigate whether trimetazidine has the protective effects against smoking-induced left ventricular remodeling in rats. In this study, Wistar rats were randomly divided into 3 groups: smoking group (exposed to cigarette smoke), trimetazidine group (exposed to cigarette smoke and treated with trimetazidine), and control group. The echocardiographic and morphometric data indicated that trimetazidine has protective effects against smoking-induced left ventricular remodeling. Oxidative stress was evaluated by detecting malondialdehyde, superoxide dismutase, and glutathione peroxidase in the supernatant of left ventricular tissue. Cardiomyocyte apoptotic rate was determined by flow cytometry with Annexin V/PI staining. Gene expression and serum levels of inflammatory markers, including interleukin-1β, interleukin-6, and tumor necrosis factor-α, were deteced by quantitative real-time PCR and enzyme-linked immunosorbent assay. Our results suggested that trimetazidine could significantly reduce smoking-induced oxidative stress, apoptosis, and inflammation. In conclusion, our study demonstrates that trimetazidine protects against smoking-induced left ventricular remodeling via attenuating oxidative stress, apoptosis, and inflammation.